Predictive factors for successful cervical ripening using a double‐balloon catheter after previous cesarean delivery. Issue 3 (29th June 2018) - Vital, Mathilde; Grange, Joséphine; Le Thuaut, Aurélie; Dimet, Jérôme; Ducarme, Guillaume
Abstract: Objective: To identify predictors of successful cervical ripening using double‐balloon catheter (DBC) for labor induction among women with previous cesarean delivery (PCD) and unfavorable cervix at term. Methods: The present prospective observational study was conducted among women who underwent cervical ripening with DBC at a French tertiary care hospital between January 1, 2014, and December 31, 2017. Inclusion criteria were PCD; singleton term fetus; cephalic presentation; and unfavorable cervix (Bishop score <6). Indications for DBC were gestational diabetes mellitus, intrahepatic cholestasis of pregnancy, pre‐eclampsia, prolonged pregnancy, fetal growth restriction, or prenatal suspicion of macrosomia. The primary outcome was Bishop score of at least six after DBC removal. Results: Among the 105 patients included, the initial Bishop score was 2.5 ± 1.5; successful cervical ripening occurred among 74 (70.5%) women; and vaginal delivery occurred among 46 (43.8%). The mean time from DBC insertion to delivery was 19.3 ± 6.7 hours. No adverse events were observed. Predictors of successful cervical ripening were initial Bishop score of at least three (adjusted odds ratio [aOR] 12.74, 95% confidence interval [CI] 2.78–58.47); PCD during labor (aOR 4.38, 95% CI 1.10–17.45); and internal cervical os open (aOR 4.94, 95% CI 1.44–17.01). Conclusion: Several factors were found to predict successful cervical ripening using DBC. Abstract : Initial Bishop score, previous cesarean delivery during labor, and internal cervical os open were predictive factors for successful cervical ripening using a double‐balloon catheter.